Facilitating the Involvement of People with Aphasia in Stroke Research by Developing Communicatively Accessible Research Resources. Issue 1 (January 2017) - Pearl, Gill; Cruice, Madeline
Abstract : People with aphasia can be marginalized by a communicatively inaccessible society. Compounding this problem, routinized exclusion from stroke research leads to bias in the evidence base and subsequent inequalities in service provision. Within the United Kingdom, the Clinical Research Network of the National Institute of Health identified this problem and funded a 6-month project in 2013–2014 that resulted in the creation of practical and freely available resources to equip researchers to engage more people with aphasia in research. Critical elements enabled authentic coconstruction of new knowledge regarding accessible research documentation, including the process structure, timescale, and crucially, the fundamental engagement of people with aphasia. Stages in this process included mapping existing resources; engaging with researchers and with people affected by aphasia; and developing a new set of resources comprising images, accessible text, and templates for research forms. These resulted in high-quality outputs, as indicated by preliminary feedback from the research community and people with aphasia. Abstract : Supplemental Digital Content is Available in the Text.